Associations of the ABCA1 and LPL Gene Polymorphisms With Lipid Levels in a Hyperlipidemic Population. (July 2018) - Tao, Fang; Weinstock, Justin; Venners, Scott A.; Cheng, Jun; Hsu, Yi-Hsiang; Zou, Yanfeng; Pan, Faming; Jiang, Shanqun; Zha, Xiangdong; Xu, Xiping
We conducted a cross-sectional study to investigate the effects of the adenosine triphosphate-binding cassette transporter 1 (ABCA1) I883M and lipoprotein lipase (LPL) HindIII polymorphisms on lipid levels in patients with hyperlipidemia. A total of 533 patients were enrolled. Serum lipid parameters were determined by an automatic biochemistry analyzer. Genotyping of the ABCA1 I883M and LPL HindIII was carried out using the polymerase chain reaction-restriction fragment length polymorphism technique. Multiple linear regression analysis was used to estimate the associations between serum lipid levels and the genetic polymorphisms. The frequency distribution of the ABCA1 I883M and LPL HindIII polymorphisms did not deviate from Hardy-Weinberg equilibrium. The major finding of our regression analysis showed that neither the ABCA1 I883M nor the LPL HindIII polymorphism was associated with baseline serum lipid levels in the total population. However, among patients with elevated alanine aminotransferase (ALT) levels (ALT ≥ 40 U/L), carriers of the M allele of the ABCA1 gene had lower levels of high-density lipoprotein cholesterol (HDL-C) and higher levels of low-density lipoprotein cholesterol (LDL-C) after adjusting for age, sex, smoking status, alcohol consumption, education level, occupation, and work intensity ( P < .05 for both). A test on interaction terms between the ABCA1 I833M polymorphism and ALT on HDL-C and LDL-C levels also remained significant ( P = .001 and P = .014, respectively). Our data suggest that there are significant interactive effects between ABCA1 I883M and ALT levels on HDL-C and LDL-C levels. However, the LPL HindIII polymorphism did not influence lipid levels.